“The Universality of Arabic Literature” (Damascus University Journal of arts and humanities sciences, 2021)
Is Arabic literature a universal or world literature? The paper is an attempt to answer such a question by discussing first the two most common definitions of world literature:• World literature is the entire world’s literatures, and• World literature is the best of what literature has to offer and that which possesses universal appeals.Critiquing both definitions for their shortcomings, the paper moves on to propose a more realistic and viable definition, based on the notion of its circulation beyond the temporal and special boundaries of its birthplace. In other worlds, world literature comprises all literary works that transcend in their circulation the limits of time and place and that overcome the barriers of language and culture.  Examining the nature and history of Arabic literature in the light of such a definition, the paper concludes by nominating this great literature for a central place in the realm of world literature.
Keywords: “The Universality of Arabic Literature”